ENLIGHT (European Network for Light Ion Hadron Therapy) and its role in Hadron therapy - Georgieva, P; Dosanjh, M (Springer, 2024)
Purpose: This study provides a comprehensive overview of the progress in hadron therapy within Europe, particularly highlighting the critical roles of the Proton Ion Medical Machine Study (PIMMS) and the European Network for Light Ion Hadron Therapy (ENLIGHT). Methods: Our approach includes a retrospective analysis of the advances in hadron therapy facilities, facilitated by a synthesis of interdisciplinary collaboration data gathered from ENLIGHT's annual meetings since 2002, and an assessment of European-funded projects and networks' contributions to the field. Results: The results showcase significant advancements in cancer treatment due to collective efforts in hadron therapy, underscored by ENLIGHT’s pivotal role in fostering interdisciplinary cooperation and the harmonization of treatment protocols across Europe. Conclusion: The evolution of hadron therapy, from its inception to its current impact on patient care, demonstrates the successful realization of complex medical technologies through sustained collaboration and standardized practices across European institutions and projects.